2023
DOI: 10.3389/fnins.2023.1131063
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortex and hippocampus neural interaction during vagus nerve stimulation under in vivo large-scale imaging

Abstract: ObjectiveThe purpose of this study was to study mechanisms of VNS modulation from a single neuron perspective utilizing a practical observation platform with single neuron resolution and widefield, real-time imaging coupled with an animal model simultaneously exposing the cerebral cortex and the hippocampus.MethodsWe utilized the observation platform characterized of widefield of view, real-time imaging, and high spatiotemporal resolution to obtain the neuronal activities in the cerebral cortex and the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Seminal articles have already shown that electrical stimulation of the whole vagus nerve (cervical level) improves learning and memory functions in both humans and rodents (Clark et al, 1999, 1998; Olsen et al, 2022; Peña et al, 2014; Sanders et al, 2019) by potentially activating the hippocampus (Xu et al, 2023) and/or by promoting hippocampal neurogenesis and plasticity-associated features (Biggio et al, 2009; Follesa et al, 2007; Olsen et al, 2022; Sanders et al, 2019). In addition, more recent studies have highlighted a clear impact of specific gut-brain vagal manipulations (selective ablations) onto hippocampal functions (O’Leary et al, 2018; Suarez et al, 2018), thus indicating that the gut represents, at least in part, a major peripheral organ with a strong vagus-mediated action onto learning and memory dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal articles have already shown that electrical stimulation of the whole vagus nerve (cervical level) improves learning and memory functions in both humans and rodents (Clark et al, 1999, 1998; Olsen et al, 2022; Peña et al, 2014; Sanders et al, 2019) by potentially activating the hippocampus (Xu et al, 2023) and/or by promoting hippocampal neurogenesis and plasticity-associated features (Biggio et al, 2009; Follesa et al, 2007; Olsen et al, 2022; Sanders et al, 2019). In addition, more recent studies have highlighted a clear impact of specific gut-brain vagal manipulations (selective ablations) onto hippocampal functions (O’Leary et al, 2018; Suarez et al, 2018), thus indicating that the gut represents, at least in part, a major peripheral organ with a strong vagus-mediated action onto learning and memory dynamics.…”
Section: Discussionmentioning
confidence: 99%